Diet selection by goats on a semi-arid shrubland in central Argentina - Pisani, J. M. (2000)
The objective of this study was to determine diet selection by goats on a semi-arid shrubland in the central part of Argentina. Ten goats grazed on a pasture for 10-days periods in winter, spring, and summer. The botanical composition of the pasture was estimated by a combined measure of cover and biomass, whereas the botanical composition of the diet was determined by the microhistological technique complemented with direct observation. Two shrub species (Condalia microphylla and Prosopis caldenia) and five soft grasses (Piptochaetium napostaense, Poa spp., Stipa tennis, S. clarazii, and Pappophorum spp.) were highly selected by goats. Shrubs represented 32%, 40% and 74% of goat diets in winter, spring and summer, respectively. For each season, the rest of goat diets was composed by the soft grasses. Although coarse grasses represented most (> 80%) of the available biomass in all seasons, they were always highly avoided by goats. The results showed that goats behave as mixed-feeders (eat grasses and shrubs) on semi-arid shrublands in central Argentina.